The agency of content creators - Erstad, Ola (Javnost (Ljubljana), 2013)
The aim of this article is to discuss some key challenges of content creation as a social and cultural practice, with agency as the analytic lens. The agency of content creators has partly been related to tensions around personal engagement using digital media, and partly about the growth of creative industries and the present economic crisis as ways of understanding transformations of content workers and employment options of young people today and in the years to come. Contemporary media developments represent both opportunities and challenges for people as content creators and the growth of creative industries and a participatory public.
Keywords: mass media; množični mediji; elektronski mediji; kreativnost